STRATEGI KEPALA SEKOLAH DALAM MENGATASI RENDAHNYA MINAT KUNJUNGAN SISWA DI PERPUSTAKAAN SMA NEGERI 11 MUARO JAMBI - Selviana Selviana; Mulyadi Mulyadi; K.A Rahman (STKIP Pesisir Selatan, 2026)
This study aims to describe the principal's strategies in addressing low student library visits at SMA Negeri 11 Muaro Jambi. This research used a qualitative approach with a case study approach. Data collection techniques included observation, interviews, and documentation. The research subjects included the principal, the head librarian, teachers, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the principal's strategy for increasing student library visits involves three main steps: providing a varied book collection tailored to student interests, optimizing the role of teachers in promoting literacy activities, and modernizing technology-based library facilities. Based on the results of research conducted on the principal's strategies in addressing low student interest in visiting the library at SMA Negeri 11 Muaro Jambi, it can be concluded that the strategies implemented by the principal have been quite effective, although not yet fully optimal. These strategies include providing a more varied book collection tailored to student needs.